Improved Silhouette Rendering and Detection of Splat-Based Models - Ivo, Rafael Fernandes; Vidal, Creto A.; Cavalcante-Neto, Joaquim B. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
Surface splatting has proven to be a good approach to render point-based models. The technique keeps the simplicity of point based models with a high quality rendering due to local filtering between the samples. However, silhouettes and sharp features are noticed as high frequency variations on image-space. Thus, filtering cannot hide artifacts to appear next to these areas without an explicit approach, mainly on bad sampling conditions as low density of samples. In this paper, we present a new curved splat approach, called here quadric splat, which improves rendering of a model near silhouette and sharp features. These quadric splats may be placed on a surface using any sampling process applying our proposed error metric. We also propose a simple method to detect splats near silhouettes on object-space. This approach allows an efficient silhouette detection on GPUs. Our silhouette detection was applied on a surface splatting pipeline aiming to render quadric splats only where their effect is more noticed, but the technique is independent and can be applied even for non-realistic rendering of splat-based models.